2018
DOI: 10.21548/40-1-2920
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Application of Steinernema yirgalemense to Control Planococcus ficus: Assessing Adjuvants to Improve Efficacy

Abstract: The vine mealybug (Planococcus ficus) is regarded as a key mealybug pest of grapevines in South Africa, with entomopathogenic nematodes (EPNs) being touted as a potential alternative to chemical control, although their vulnerability to above-ground environmental conditions has limited their use. In this study, tests were conducted to assess the ability of adjuvants to increase the deposition of S. yirgalemense on grapevine leaves. The combination of Nu-Film-P ® and Zeba ® resulted in significantly more infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…Applying S. yirgalemense in combination with both adjuvants on P. ficus infested leaf discs in a growth chamber, resulted in 84% mortality. Similar results were observed in a glasshouse trial, with 88% control of P. ficus on leaf discs hung on potted vines (Platt et al, 2018b). These studies demonstrated the potential of a combination of S. yirgalemense and adjuvants to give significant control of P. ficus on grapevine foliage in semi-natural conditions on vine leaves.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…Applying S. yirgalemense in combination with both adjuvants on P. ficus infested leaf discs in a growth chamber, resulted in 84% mortality. Similar results were observed in a glasshouse trial, with 88% control of P. ficus on leaf discs hung on potted vines (Platt et al, 2018b). These studies demonstrated the potential of a combination of S. yirgalemense and adjuvants to give significant control of P. ficus on grapevine foliage in semi-natural conditions on vine leaves.…”
Section: Introductionsupporting
confidence: 82%
“…The different treatments applied include, Zeba ® only, Zeba ® + Nu-Film-P ® and nematodes without adjuvants, with a control of water only (without adjuvants). In a previous study, Platt et al (2018b) showed that Nu-Film-P ® alone did not significantly improve the deposition of IJ on grapevine leaves, over the applications of Zeba alone and therefore was not included as a separate treatment. Treatments were applied to the Petri dishes via a calibrated handheld sprayer, after which the leaves were removed and left for 3 min to eliminate excess runoff.…”
Section: Adjuvant Field Trialmentioning
confidence: 99%
“…More nematode species, especially H. zealandica and other native species that show effective control against lepidopteran pests, can be evaluated in future research to establish a nematode susceptibly profile for L. vanillana . In addition, the application of nematode formulations to the canopy and soil of orchards may have the ability to control multiple pests simultaneously [22,25,26,44–46], especially when used in an integrated pest management programme.…”
Section: Discussionmentioning
confidence: 99%
“…Insects without a soil stage may be more susceptible to EPNs, as they may not have had the opportunity to evolve the resistance necessary to protect themselves from nematode infections. This weakness of above-ground pest defence mechanisms against microbiological pathogens can thus be exploited to provide biological control, for example, as with previous research on mealybugs, and the addition of adjuvants to nematode suspensions [18,[22][23][24][25][26] has…”
Section: Introductionmentioning
confidence: 99%
“…However, infectivity of S. yirgalemense was deeply affected by temperature and, above all, relative humidity, as mortality rates decreased from 70 to 40% when RH decreased from 100 to 60% (Platt et al 2018). Therefore, laboratory and glasshouse experiments were carried out with the aim to increase the nematode survival and infectivity in foliar applications by adding adjuvants, such as polysaccharide starch and spreader (Platt et al 2019). Addition of adjuvants concurred to increase mortality of P. ficus females by S. yirgalemense to 88% compared with nematode application with water alone.…”
Section: Nematodesmentioning
confidence: 99%